Effect of Au/HfS3 interfacial interactions on properties of HfS3-based devices. Issue 22 (31st May 2022) - Dhingra, Archit; Lipatov, Alexey; Loes, Michael J.; Abourahma, Jehad; Pink, Maren; Sinitskii, Alexander; Dowben, Peter A.
Abstract : N-type HfS3 in vacuo (left) versus p-type HfS3 in air (right); O2 chemisorption changes the n-type E F to p-type E F . Abstract : X-ray photoemission spectroscopy (XPS) has been used to examine the interaction between Au and HfS3 at the Au/HfS3 interface. XPS measurements reveal dissociative chemisorption of O2, leading to the formation of an oxide of Hf at the surface of HfS3 . This surface hafnium oxide, along with the weakly chemisorbed molecular species, such as O2 and H2 O, are likely responsible for the observed p-type characteristics of HfS3 reported elsewhere. HfS3 devices exhibit n-type behaviour if measured in vacuum but turn p-type in air. Au thickness-dependent XPS measurements provide clear evidence of band bending as the S 2p and Hf 4f core-level peak binding energies for Au/HfS3 are found to be shifted to higher binding energies. This band bending implies formation of a Schottky-barrier at the Au/HfS3 interface, which explains the low measured charge carrier mobilities of HfS3 -based devices. The transistor measurements presented herein also indicate the existence of a Schottky barrier, consistent with the XPS core-level binding energy shifts, and show that the bulk of HfS3 is n-type.